Paternal High-Fat Diet Altered Sperm 5'tsRNA-Gly-GCC Is Associated With Enhanced Gluconeogenesis in the Offspring - Wang, Bin; Xia, Lin; Zhu, Dan; Zeng, Hongtao; Wei, Bin; Lu, Likui; Li, Weisheng; Shi, Yajun; Liu, Jingliu; Zhang, Yunfang; Sun, Miao (Frontiers in Molecular Biosciences, 2022)
Background: Paternal lifestyle, stress and environmental exposures play a crucial role in the health of offspring and are associated with non-genetic inheritance of acquired traits, however the underlying mechanisms are unclear. In this study, we aimed to find out how the sperm tsRNA involved in paternal high-fat diet induced abnormal gluconeogenesis of F1 offspring, and explore the underlying molecular mechanism of its regulation. Method: We generated a paternal high fat diet (42% kcal fat) model to investigate the mechanism by which paternal diet affects offspring metabolism. Four-week-old C57BL/6J male mice were randomly assigned into two groups to receive either a control diet (CD; 10% kcal fat) or a high-fat (HFD; 42% kcal fat) diet for 10 weeks, and mice from each group were then mated with 8-week-old females with control diet in a 1:2 ratio to generate F1. F0 sperms were isolated and small RNAs was sequenced by high-throughput sequencing. Metabolic phenotypes were examined with both F0 and F1. Results: A significant increase in body weight was observed with HFD-F0 mice at 8 weeks of age as compared to CD mice at the same age. F0 mice showed impaired glucose tolerance (GTT), resistance to insulin tolerance (ITT) and increased pyruvate tolerance (PTT) at 14 weeks. HFD-F1 male mice showed no significant difference in body weight. An increase in PTT was found at 13 weeks of age and no significant changes in GTT and ITT. PEPCK and G6Pase that related to gluconeogenesis increased significantly in the liver of HFD-F1 male mice. Sperm sequencing results showed that 5'tsRNA-Gly-GCC derived from tRNA-Gly-GCC-2 specifically was remarkably upregulated in sperm of HFD F0 mice. Q-PCR further showed that this tsRNA was also increased in the liver of HFD-F1 comparison with CD-F1 mice. In addition, we found that 5'tsRNA-Gly-GCC can regulate Sirt6-FoxO1 pathway and be involved in the gluconeogenesis pathway in liver. Conclusion: 5'tsRNA-Gly-GCC that increased in HFD mice mature sperms can promote gluconeogenesis in liver by regulating Sirt6-FoxO1 pathway, which might represent a potential paternal epigenetic factor mediating the intergenerational inheritance of diet-induced metabolic alteration.